Closed Displaced tibial Shaft Fractures in Children : Comparison between Casting and Operative Treatment With Flexible Intramedullary Nails - الاسمر علام; يوسف صفوان; جوني أحمد (Latakia University Journal -Medical Sciences Series, 2022)
Objective: evaluate the functional outcomes and union for tibial shaft fractures in children between casting and operative treatment using flexible intramedullary nails. Patients and methods: A retrospective-prospective study included 43 children between 4-14 years old. The children was divided ​​into 2 groups (conservative and operative). Flynn score was performed after one year. The duration of the research was three years, from February 2019 to February 2022. Results: there was no statistically difference between the two groups of overall results according to Flynn`s score , and the results were excellent in the vast majority of patients. Excellent results were higher in males. the results of proximal third were better than the middle and distal third. Healing was better in the younger group, spiral and oblique fractures, also when there is an accompanying fibula fracture . Conclusion: since the incidences of delayed union and infection were higher in patients treated surgically. We recommend to use the conservative treatment as the first line in the treatment of closed displaced tibial shaft fractures in children , and not to delay of using surgical treatment in cases of failure of closed treatment or when there is an indication for surgery.